Pendampingan Belajar Bahasa Arab Melalui Pendalaman Materi Pada Anak di TPQ Miftahul Ulum Desa Sidoharjo Kecamatan Pulung Ponorogo - Sulton Azali Amrullah; Medina Nur Asyifa Purnama (Social Science Academic, 2023)
This article is motivated by a lack of ability in learning Arabic, both writing and others. This assistance aims to guide children in learning Arabic at the elementary level in particular. The object or target in this assistance is TPA children consisting of kindergarten to elementary/MI. The method used is Asset Based Community Development (ABCD). In carrying out this assistance, namely with a learning assistance model that is carried out for 1 month. The material provided includes Vocabulary, Arabic Rules, Kitabah, Qiro'ah, Javanese Pegon Arabic, and other Religious Materials. The result of this assistance is Improving Children's Ability in Arabic Learning Proficiency Through Providing Materials for Introducing Arabic to Elementary Level Religious Materials. As well as the role and importance of this assistance activity, it received a very positive response from the TPA, because this assistance is in accordance with the needs of children and they are very enthusiastic. It can be concluded that there are efforts in Assistance activities at TPQ to develop and improve Children's abilities in Arabic Language Mastery both Writing and Reading Ability.